PENGARUH KUALITAS PELAYANAN, KUALITAS PRODUK, DAN WORD OF MOUTH COMMUNICATION TERHADAP KEPUTUSAN PEMBELIAN PADA RM GARANG ASEM SARI RASA (Studi pada Konsumen RM Garang - Putri, Citra Aprilliani; Waluyo, Handoyo Djoko; Listyorini, Sari (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2016)
RM Garang Asem Sari Rasa is a traditional restaurant. However, the advantages offered by this restaurant is considered suboptimal. Many of the complaints submitted by cosumers to the company, among others regarding who are less tham satisfactory, and etc. So that these things will obviously influence purchase decisions. The purpose of this study was to determine the effect of service quality, product quality, and word of mouth communication to purchase decision in RM Garang Asem Sari Rasa consumer RM Garang Asem Sari Rasa, Kudus. This type of research is explanatory research. The population in this research that consumers RM Garang Asem Sari RasaÂ and the number of samples taken was 100 respondents. The sampling technique in this study using a non-probability sampling with purposive sampling technique. The analytical method used is cross tabulation, correlation, determination, simple linear regression, multiple, t test and F test with SPSS version 16.Based on the survey results revealed that the quality service, product quality, and word of mouth communication provides a positive and significant influence on purchase decision, either partially or simultaneously. Independent variables that have the most influence on purchase decision is variable word of mouth communication. The advice that can be given is to give training to employees, improving hygiene in the dining area, increasing the neatness on every employee using a uniform, always keeping and improving the selection of raw materials to keep it fresh, adjust the portion of food that is always the same, improve service so that consumers feel deserve to recommend to the people around him.